2022
DOI: 10.1038/s41467-022-31100-1
|View full text |Cite
|
Sign up to set email alerts
|

A Catharanthus roseus Fe(II)/α-ketoglutarate-dependent dioxygenase catalyzes a redox-neutral reaction responsible for vindolinine biosynthesis

Abstract: The Madagascar’s periwinkle is the model plant for studies of plant specialized metabolism and monoterpenoid indole alkaloids (MIAs), and an important source for the anticancer medicine vinblastine. The elucidation of entire 28-step biosynthesis of vinblastine allowed further investigations for the formation of other remarkably complex bioactive MIAs. In this study, we describe the discovery and characterization of vindolinine synthase, a Fe(II)/α-ketoglutarate-dependent (Fe/2OG) dioxygenase, that diverts asse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 40 publications
1
12
0
Order By: Relevance
“…The only exceptions we found were threonine and malic acid, which were higher in the shaded than in the NL plants. These are partly in agreement with the idea that, besides their role as precursors of proteins, amino acids can also be catabolized to generate energy when photosynthesis does not meet the plant's energy demands (Galili et al 2014).…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…The only exceptions we found were threonine and malic acid, which were higher in the shaded than in the NL plants. These are partly in agreement with the idea that, besides their role as precursors of proteins, amino acids can also be catabolized to generate energy when photosynthesis does not meet the plant's energy demands (Galili et al 2014).…”
Section: Discussionsupporting
confidence: 87%
“…In order to follow the effects of different growth light conditions from the primary light intensity dependent processes (i.e., photosynthetic processes and primary metabolites) to the secondary metabolic processes, further detailed chromatographic investigations were carried out. The synthesis of phenolic compounds, including flavonoids in plants, is influenced by various environmental factors, especially light (Ghasemzadeh et al 2010, Xu et al 2020, Sutulienė et al 2022. Flavonoids are well-known antioxidant compounds that play a role in photoprotection as well.…”
Section: Discussionmentioning
confidence: 99%
“…The identifications of the demethyldihydrocorynantheine/demethylcorynantheidine synthases (DCSs) were based on previous characterizations of these short/medium chain dehydrogenase type reductases from C. roseus and Cinchona pubescens (Fig. 2a; Qu et al ., 2015, 2017, 2018a,b; Stavrinides et al ., 2016; Tatsis et al ., 2017; Eng et al ., 2022). The recombinant enzymes clearly showed great plasticity in their reduction product spectra since every enzyme produced multiple products, comparable to the well‐known structural diversity of the strictosidine aglycones that exist in equilibrium (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Catharanthine ( 127 ), vindoline ( 129 ), and vindolinine ( 130 and 131 ) are the three most abundant monoterpenoid indole alkaloids in Catharanthus roseus (Scheme A). Catharanthine ( 127 ) and tabersonine ( 128 ), a precursor to vindoline ( 129 ), are biosynthesized via cycloaddition reactions with the common intermediate dehydrosecodine ( 126 ) that are catalyzed by HL1 and HL2, respectively. , Recent gene silencing experiments, transient gene expression, and in vitro assays of the gene products demonstrated that the Fe­(II)/αKG-dependent enzyme VNS (vindolinine synthase) and HL2 are responsible for the production of the pair of epimers 130 and 131 and the side product 132 from the shared biosynthetic intermediate 126 (Scheme A) . Due to the instability of 126 , direct tests of the activity of VNS alone were not conducted.…”
Section: Mononuclear Nonheme Iron Enzymesmentioning
confidence: 99%
“…157,158 Recent gene silencing experiments, transient gene expression, and in vitro assays of the gene products demonstrated that the Fe(II)/αKG-dependent enzyme VNS (vindolinine synthase) and HL2 are responsible for the production of the pair of epimers 130 and 131 and the side product 132 from the shared biosynthetic intermediate 126 (Scheme 14A). 159 Due to the instability of 126, direct tests of the activity of VNS alone were not conducted. However, the combined enzyme assay with HL2 in the presence of αKG and ascorbate suggested that VNS catalyzed the redox-neutral reaction of 126.…”
Section: Introductionmentioning
confidence: 99%